IMPLEMENTASI PEMBELAJARAN PENDIDIKAN KEWARGANEGRAAN BERBASIS KARAKTER BAGI PENGEMBANGAN KEMANDIRIAN PESERTA DIDIK DI SMA - Rianto, Hadi (Sosio Religi: Jurnal Kajian Pendidikan Umum, 2016)
This research for development aspects of autonomy through learning Civics character-based, with the aim to obtaining factual overview of the learning process implementation at school. This study used a qualitative approach with descriptive methods. Collected data through observation, interviews, literature studies and documentation. This research studies starting from the preparation of the planning, execution, and results are displayed behaviors and attitudes of students after participating in the learning process. From this study it was found that participants were able to show the reflects of behavioral autonomy aspects throught behavior and attitude in school, family and community.